Narrativas Sobre Creencias Familiares, Violencia Intergeneracional e Historias de las Relaciones Parentales en tres Madres del Municipio de Soacha (2024)
The present research was carried out with the objective of analyzing the narratives about family beliefs, intergenerational violence and stories of parental relationships in three Mothers from the Municipality of Soacha" it used a qualitative approach of narrative biographical case study to explore the experiences of three mothers in In relation to their family beliefs, intergenerational violence and the dynamics of parental relationships, the study used free interviews as the main method of data collection, allowing the participants to relate their experiences in an open and reflective manner.